Rapid whole‐blood assay to detect SARS‐CoV‐2‐specific memory T‐cell immunity following a single dose of AstraZeneca ChAdOx1‐S COVID‐19 vaccine. Issue 8 (12th August 2021) - Lineburg, Katie E; Neller, Michelle A; Ambalathingal, George R; Le Texier, Laetitia; Raju, Jyothy; Swaminathan, Srividhya; Lekieffre, Lea; Smith, Caitlyn; Rehan, Sweera; Crooks, Pauline; Panikkar, Archana; Srihari, Sriganesh; et al.
Abstract: Objectives: With the ongoing emergence of SARS‐CoV‐2 variants and potential to evade vaccine‐induced neutralisation, understanding the magnitude and breadth of vaccine‐induced T‐cell immunity will be critical for the ongoing optimisation of vaccine approaches. Strategies that provide a rapid and easily translatable means of assessing virus‐specific T‐cell responses provide an opportunity to monitor the impact of vaccine rollouts in the community. In this study, we assessed whether our recently developed SARS‐CoV‐2 whole‐blood assay could be used effectively to analyse T‐cell responses following vaccination. Methods: Following a median of 15 days after the first dose of the ChAdOx1‐S (AstraZeneca ® ) vaccine, peripheral blood was isolated from 58 participants. Blood was incubated overnight with an overlapping set of spike protein peptides and assessed for cytokine production using a cytometric bead array. Results: The majority of vaccine recipients (51/58) generated a T helper 1 response (IFN‐γ and/or IL‐2) following a single dose of ChAdOx1‐S. The magnitude of the IFN‐γ and IL‐2 response strongly correlated in vaccine recipients. While the production of other cytokines was evident in individuals who did not generate IFN‐γ and IL‐2, they showed no correlation in magnitude, nor did we see a correlation between sex or age and the magnitude of the response. Conclusions: The whole‐blood cytokine assay provides a rapid approach to assessing T‐cell immunity against SARS‐CoV‐2 in vaccine recipients. While the majority of participants generated a robust SARS‐CoV‐2‐specific T‐cell response following their first dose, some did not, demonstrating the likely importance of the booster dose in improving T‐cell immunity. Abstract : Strategies that provide a rapid and easily translatable means of assessing SARS‐CoV‐2‐specific T‐cell responses provide an opportunity to monitor the impact of vaccine rollouts in the community. In this study, we assessed whether our recently developed SARS‐CoV‐2 whole‐blood assay could be used effectively to analyse T‐cell responses following vaccination. We demonstrated that the whole‐blood cytokine assay provides a rapid approach to assessing T‐cell immunity against SARS‐CoV‐2 in vaccine recipients.